Does physical exercise improve quality of life in patients with fibromyalgia? - Sieczkowska S.M.* (2020)
© 2019, Royal Academy of Medicine in Ireland.Background: To compare patients with active and inactive fibromyalgia to better understand the impact of physical inactivity on quality of life and symptoms in these patients. Methods: A total of 304 patients were eligible for the study, 20 were excluded for reasons of health, work, or unavailability to perform the collection. Data were collected to assess sociodemographic and clinical characteristics, physical exercise, sleep, and quality of life. Patients were classified as active (performed physical exercise) or inactive (did not perform physical exercise). Sleep was assessed using the Pittsburgh Sleep Quality Index and quality of life was assessed using the Fibromyalgia Impact Questionnaire. Results: Of the 284 final participants, 97.9% were women, with a mean age of 50.39 ± 10.31 years. Most did not exercise regularly and did not work, and most used antidepressant drugs and muscle relaxants. Patients who exercised regularly had a better overall quality of life than those who did not; moreover, inactive patients had a 1.77-fold likelihood of a greater impact on quality of life, and those with poor sleep quality had a 10.79-fold likelihood. Conclusions: Our results reinforce the understanding that exercise can reduce symptoms of fibromyalgia and suggests that patients who practice physical exercise have a better quality of life, with fewer depressive symptoms and absences from work, and better sense of well-being.